1996
DOI: 10.1111/j.1547-5069.1996.tb01201.x
|View full text |Cite
|
Sign up to set email alerts
|

Problem‐Focused Coping in HIV‐Infected Mothers in Relation to Self‐Efficacy, Uncertainty, Social Support, and Psychological Distress

Abstract: A preliminary investigation of relationships among perceived self-efficacy, uncertainty, social support, psychological distress, and problem-focused coping was conducted in a convenience sample of 41 HIV-infected mothers. The mothers represented 93% of the clients in a large HIV clinic in 1992 who met the study criteria. Support was found for using Lazarus and Folkman's stress, appraisal, and coping framework to understand the health-related needs of HIV-infected mothers. Maternal coping was related to living … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 24 publications
1
15
1
Order By: Relevance
“…15 Since self-efficacy is content-specific, the scales measuring self-efficacy in one illness can not be used in another illness. A number instruments measure self-efficacy in the context of HIV/AIDS, including measures of self-efficacy to reduce high HIV risk behaviors, 16,17 to disclose HIV status to sexual partner, 18,19 to cope with HIV/AIDS, 20,21 to improve medication adherence, 11 and to manage the chronic disease by oneself. 22 A number of reports have revealed close relationships between self-efficacy and specific behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…15 Since self-efficacy is content-specific, the scales measuring self-efficacy in one illness can not be used in another illness. A number instruments measure self-efficacy in the context of HIV/AIDS, including measures of self-efficacy to reduce high HIV risk behaviors, 16,17 to disclose HIV status to sexual partner, 18,19 to cope with HIV/AIDS, 20,21 to improve medication adherence, 11 and to manage the chronic disease by oneself. 22 A number of reports have revealed close relationships between self-efficacy and specific behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Sharts-Hopko et al (1996) found that the perceived cost of social support (as measured by the short form of the Interpersonal Relationship Inventory; Tilden, 1991) was inversely associated with psychological distress among HIV-positive mothers; however, this has not been included among reported negative associations in the section "Results", since it is a distinct concept from extent or level of social support and therefore may be confusing. A possible explanation offered by the authors is that the ability to recognize the costs of social support may be an indicator of coping or at least of a lesser degree of neediness (Sharts-Hopko et al, 1996). In addition, Leslie et al (2002) found greater social support, as mediated through coping strategies, to have an indirect positive effect on health-care satisfaction and an indirect negative effect on substance use.…”
Section: Notesmentioning
confidence: 90%
“…Four of the 15 studies reviewed did not find any significant relationship between the social support dimensions and the health outcomes measured (Leslie, Stein, & Rotheram-Borus, 2002;Miles, Burchinal, Holditch-Davis, Wasilewski, & Christian, 1997;Murphy et al, 2002;Sharts-Hopko, Regan-Kubinski, Lincoln, & Heverly, 1996). 3 The remaining 11 studies found one or more of the following significant associations: (1) direct associations between social support and physical health (one study); (2) direct associations between social support and mental health (10 studies); and (3) indirect associations between social support and mental health through coping processes (three studies).…”
Section: Study Findingsmentioning
confidence: 91%
“…The family is a particularly important source of support in the African American community (Benin and Keith, 1995;Greenwood et al, 1996b;Neighbors, 1997;Taylor et al, 1997). Young recent mothers generally (Sacco and Macleod, 1990;Barratt et al, 1996) and HIV-infected recent mothers specifically (Sharts-Hopco et al, 1996) have shown an inverse relationship between the level of available social support and various indicators of psychological distress.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…The family is a particularly important source of support in the African American community (Benin and Keith, 1995;Greenwood et al, 1996b;Neighbors, 1997;Taylor et al, 1997). Young recent mothers generally (Sacco and Macleod, 1990;Barratt et al, 1996) and HIV-infected recent mothers specifically (Sharts-Hopco et al, 1996) have shown an inverse relationship between the level of available social support and various indicators of psychological distress.Perceived control is a resource internal to the individual that involves the individual's perception of the amount of influence she has over the events in her life. Feelings of control have generally been inversely related to indicators of psychological distress (Pearlin and Schooler, 1978;Pearlin et al, 1981;Mirowsky and Ross, 1990;Miller, et al, 1995;Ali and Avison, 1997).…”
mentioning
confidence: 99%